19th century American utopias as destratification experiments - Schwartz, T. P. (The Greek Review of Social Research, 1974)
The destratification experiences of a number of the more important 19th century American utopias, with emphasis on the Oneida and Shaker communities, are described and are evaluated as to individual and communal costs and benefits. While these utopian ventures were often quite successful as destratification experiments, at least for brief periods of time, the factors that contributed to this success, and the factors that contributed to the longterm viability of the communities as social systems, were often antithetical. The implications of this study concerning a number of important issues in stratification theory are discussed.